Development, validation, and cut-off points for a questionnaire to measure sources of stress in veterinary medicine (SOS-VetMed) - A. Osca; L. Millán; L. Vela; J. Barrado (BMC Public Health, 2024)
Abstract Background Occupational stress is a serious problem in veterinary medicine; however, validated instruments to measure this problem are lacking. The aim of the current study was to address this literature gap by designing and validating a questionnaire and establishing the cut-off points for identifying veterinarians with high and low levels of stress. Methods The study involved two sub-studies with two Spanish samples. The first study (N = 30 veterinarians; 66.7% women; 63.33% from small animal clinics) investigated the factors related to the work environment that caused the most stress; the results were analyzed using thematic content analysis. The second study (N = 1082; 70.8% women; 71.4% from small animal clinics) involved designing and validating a questionnaire to measure sources of stress in veterinary medicine, as well as establishing the cut-off points for interpreting the results using receiver operating characteristics (ROC) curve analysis. Results The first study showed the main sources of stress and allowed items to be defined for the questionnaire. The second study validated the Sources of Stress in Veterinarian Medicine (SOS-VetMed) questionnaire and confirmed five sources of stress with adequate reliability and validity indices: “work overload,” “work–family conflict,” “emotional burden of work,” “organizational factors,” and “emergency problems.” Exploratory and confirmatory factor analyses verified a structure of five factors (Cronbach’s alpha values ranging between 0.92 and 0.69). The five subscales of the SOS-VetMed questionnaire were positively correlated with two indicators of distress: “psychological complaints” and “psychosomatic complaints.” The cut-off points indicated that 45.83% and 19.95% of the veterinarians surveyed had high and low levels of stress, respectively. Conclusions The results confirmed that the SOS-VetMed questionnaire could be used to determine the stress levels of veterinarians and to design intervention programs to improve their workplace health.